2021
DOI: 10.30802/aalas-jaalas-20-000029
|View full text |Cite
|
Sign up to set email alerts
|

West Nile Virus Seroprevalence in an Outdoor Nonhuman Primate Breeding Colony in South Florida

Abstract: West Nile virus (WNV) was first detected in Florida in July 2001, with 404 human cases reported to the Centers for Disease Control and Prevention as of February 2020. The subtropical climate of Florida is ideal for the mosquitoes that transmit WNV. We investigated the WNV seroprevalence in 3 NHP species housed outdoors at The Mannheimer Foundation in South Florida. From January to December 2016, 520 3 to 30 y old NHP were sampled at our 2 closed sites in Homestead and LaBelle:200 rhesus macaques (Macaca mulatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…This mosquito species was reported to have a relative abundance of 13%. Based on a 2016 surveillance in Miami, Florida, WNV immunoglobulin G was found in Macaca mulatta, M. fascicularis, and Papio hamadryas [26]. Serological tests on mosquito salivary protein on M. mulatta and Erythrocebus patas found that Cx.…”
Section: Discussionmentioning
confidence: 99%
“…This mosquito species was reported to have a relative abundance of 13%. Based on a 2016 surveillance in Miami, Florida, WNV immunoglobulin G was found in Macaca mulatta, M. fascicularis, and Papio hamadryas [26]. Serological tests on mosquito salivary protein on M. mulatta and Erythrocebus patas found that Cx.…”
Section: Discussionmentioning
confidence: 99%
“…The parasite's infectious stage is transmitted through the bug's feces, contaminating successive hosts' bite wounds or surrounding mucosal membranes. In addition, oral transmission in animals occurs when they consume infected insects (Barr 2009;Dorn et al 2012;Rocha et al 2013;Desquesnes 2017;Hodo et al 2018). Congenital transmission, blood transfusions, and organ transplants are additional methods of transmission.…”
Section: Trypanosoma Cruzimentioning
confidence: 99%